RNA in situ hybridization for human papillomavirus testing in oropharyngeal squamous cell carcinoma on a routine clinical diagnostic platform. (1st September 2020) - Henley‐Smith, Rhonda; Santambrogio, Alice; Andoniadou, Cynthia L.; Odell, Edward; Thavaraj, Selvam
Abstract : Background: The current diagnostic standard for detection of high‐risk human papillomavirus (HPV) in oropharyngeal squamous cell carcinoma is via a two‐stage algorithm, namely p16 immunohistochemistry followed by HPV DNA in situ hybridization in p16 positive cases. This study evaluated the feasibility of automated RNA in situ hybridization on a clinical platform as a single‐step alternative to the two‐stage algorithm within a routine diagnostic histopathology setting. Methods: Thirty‐eight cases positive for both p16 and DNA in situ hybridization, 42 p16 negative cases and 20 cases positive for p16 but negative for DNA in situ hybridization were randomly selected. High‐risk HPV RNA in situ hybridization was undertaken on all cases on an automated clinical platform. Manufacturer‐recommended and on‐slide additional p16/HPV positive and negative controls were used. Test quality assurance and diagnostic RNA in situ hybridization were independently assessed by two observers. A consensus diagnosis was reached in the presence of a third observer on discordant cases. All RNA in situ hybridization results were then correlated against p16 and DNA ISH status. Results: Inter‐slide RNA in situ hybridization staining variation was observed in control sections. RNA in situ hybridization demonstrated a high inter‐observer agreement rate ( κ = .897, P < .001). Following consensus review, there was full concordance between RNA in situ hybridization and the current standard. Conclusion: Human papillomavirus testing by standalone automated RNA in situ hybridization on a clinical diagnostic platform currently available in routine diagnostic histopathology laboratories is a feasible alternative to the two‐step algorithm of p16 and DNA in situ hybridization. Control tissue staining procedures need to be adapted to achieve the most accurate results.